2015
DOI: 10.1108/ijge-05-2014-0016
|View full text |Cite
|
Sign up to set email alerts
|

Gender and the use of external business advice: a Swedish study

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 80 publications
0
7
0
1
Order By: Relevance
“…An interesting study by Ozkanli and White (2009) observes that in both Turkish and Australian universities, some women have difficulty in getting into senior management positions. Results of Yazdanfar and Abbasian's (2015) study indicate that gender may be an important variable in the use of advice among small business owners in Sweden. Female owners appear to be more eager than male owners to use external business advice and do so to a higher extent.…”
Section: The Issue Of Gendermentioning
confidence: 93%
“…An interesting study by Ozkanli and White (2009) observes that in both Turkish and Australian universities, some women have difficulty in getting into senior management positions. Results of Yazdanfar and Abbasian's (2015) study indicate that gender may be an important variable in the use of advice among small business owners in Sweden. Female owners appear to be more eager than male owners to use external business advice and do so to a higher extent.…”
Section: The Issue Of Gendermentioning
confidence: 93%
“…Ahl and Nelson () compare United States and Swedish women entrepreneurship's policies and report that economic growth rather than gender equality is the principal motivation of such policies. However, Ahl et al’s () review suggests that in Nordic countries, women's entrepreneurship policy has evolved over time, conceptualizing and discussing challenges faced by “ FemInc.ism ,” which they define as “feminist action through enterprise.” Finally, Yazdanfar and Abbasian's () survey found significantly higher uptake of advice by women than men in Sweden, with gender differentials in advice also being reported by other authors such as Scott and Irwin () and Robson, Jack, and Freel (). Terjesen, Bosma, and Stam's () review of public policy for various types of entrepreneurs suggests that women represent about a third of entrepreneurs and tend to establish undercapitalized and less growth‐oriented businesses.…”
Section: Entrepreneurial Finance: Applying Intersectionalitymentioning
confidence: 57%
“…A primary preoccupation of policy for women entrepreneurs has and continues to be resources, for example, finance (see, e.g., Wilson, Whittam, & Deakins, ). Policy for women in Nordic countries, primarily adopting feminist approaches (Ahl, Berglund, Pettersson, & Tillmar, ; Ahl & Nelson, ; Pettersson, Ahl, Berglund, & Tillmar, ; Yazdanfar & Abbasian, ), has been extensively reviewed. Pettersson et al () found that economic growth, which they attribute to be “non‐feminist” with women considered as resources to be exploited, is a primary objective of much entrepreneurship policy.…”
Section: Entrepreneurial Finance: Applying Intersectionalitymentioning
confidence: 99%
“…Adopting a gender-focused approach to small business support is essential to ensure support services meet the needs of all entrepreneurs. On average, women entrepreneurs seek and prefer different kinds of advice to men, and seek more advice, particularly in the early stages of venture creation (Yazdanfar and Abbasian, 2015;EIGE, 2017).…”
Section: Policy Issue: Creating a Gender-focused Business Support Eco-systemmentioning
confidence: 99%